The GLINT South testbed for nulling interferometry with photonics: Design and on-sky results at the Anglo-Australian Telescope. (9th August 2021) - Lagadec, T.; Norris, B.; Gross, S.; Arriola, A.; Gretzinger, T.; Cvetojevic, N.; Martinod, M.-A.; Jovanovic, N.; Withford, M.; Tuthill, P.
Abstract: In 1978, Bracewell suggested the technique of nulling interferometry to directly image exoplanets which would enable characterisation of their surfaces, atmospheres, weather, and possibly determine their capacity to host life. The contrast needed to discriminate starlight reflected by a terrestrial-type planet from the glare of its host star lies at or beyond a forbidding $10^{-10}$ for an exo-Earth in the habitable zone around a Sun-like star at near-infrared wavelengths, necessitating instrumentation with extremely precise control of the light. Guided Light Interferometric Nulling Technology (GLINT) is a testbed for new photonic devices conceived to overcome the challenges posed by nulling interferometry. At its heart, GLINT employs a single-mode nulling photonic chip fabricated by direct-write technology to coherently combine starlight from an arbitrarily large telescope at 1 550 nm. It operates in combination with an actuated segmented mirror in a closed-loop control system, to produce and sustain a deep null throughout observations. The GLINT South prototype interfaces the 3.9-m Anglo-Australian Telescope and was tested on a sample of bright Mira variable stars. Successful and continuous starlight injection into the photonic chip was achieved. A statistical model of the data was constructed, enabling a data reduction algorithm to retrieve contrast ratios of about $10^{-3}$ . As a byproduct of this analysis, stellar angular diameters that were below the telescope diffraction limit ( $\sim$ 100 mas) were recovered with 1 $σ$ accuracy and shown to be in agreement with literature values despite working in the seeing-limited regime. GLINT South serves as a demonstration of the capability of direct-write photonic technology for achieving coherent, stable nulling of starlight, which will encourage further technological developments towards the goal of directly imaging exoplanets with future large ground based and space telescopes.